Digital Marketing Trends and Innovations in Indonesia: A Qualitative Exploration of Emerging Practices - Abdul Ahmad Hafidh Nurmansyah; Agus Rahayu; Heny Hendrayati (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This qualitative research explores the evolving landscape of digital marketing trends and innovations in Indonesia. Against the backdrop of rapid technological advancements and a growing digital consumer base, this study aims to shed light on the current state of digital marketing practices in the Indonesian context. To achieve this, an in-depth qualitative approach was employed, involving interviews and content analysis of leading industry professionals and digital marketing campaigns. The findings reveal a dynamic environment characterized by the adoption of cutting-edge technologies such as artificial intelligence, influencer marketing, and personalized content strategies. Additionally, the study identifies the increasing significance of social responsibility and ethical considerations in digital marketing campaigns, reflecting a growing awareness among businesses to align with societal values. This research not only contributes to the existing body of knowledge on digital marketing trends but also provides valuable insights for businesses and marketers looking to navigate the Indonesian market's unique challenges and opportunities in the digital era.